Student profile, first job library type preference and library compensation and competitive atmosphere - Cruz, Cirilo Jr. B. (2001)
This study has sought to determine if there is a relation between the library type, and the compensation and competitive atmosphere attributed to it using Kendall's W Test. It also ascertained if there is a link between undergraduate and graduate BLIS respondent profiles and their first job library type preferences through the Independent Samples T-Test. In addition, it surveyed the actual first job library types and corresponding profiles of the graduates from the Institute. The survey questionnaire was used to gather both student and graduate profiles, Competitive atmosphere and compensation rankings , library type preference rankings, and actual first job library types of the graduates from the Institute. Curriculum Weighted Averages (CWA) for both respondent categories were obtained from the Administration Office.